We make our own history : Marxism and social movements in the twilight of neoliberalism - Cox, Laurence; Nilsen, Alf Gunvald (London : Pluto Press, 2014)
A rethinking of popular political movements, this book looks at new, emerging, mass visions and analyses their impact and potential in new ways.
"The this-worldliness of their thought': social movements and theory -- 'History does nothing': the primacy of praxis in movement theorising -- 'The authors and the actors of their own drama': a Marxist theory of social movement -- 'The bourgeoisis, historically, has played a most revolutionary part': social movements from above and below in historical capitalism -- 'The point is to change it': movements from below against neoliberalism.
Includes bibliographical references and index.
Keywords: Socialism; Social movements; Neoliberalism; Marxian school of sociology; Politics; Socialism; Marxian school of sociology; Neoliberalism; Social movements; Socialism; Marxismus; Neoliberalismus; Soziale Bewegung